Multilayer Electrospun Poly(l>-Lactic Acid)/Polyacrylonitrile (PLLA/PAN) Mesoporous Matrices: Structural Design and Properties - Garcia-Herrera, C (American Chemical Society, 2025)
This study reports the development and characterization of hierarchical mesoporous electrospun scaffolds based on poly(l-lactic acid) (PLLA) and polyacrylonitrile (PAN) fabricated through a multilayer (five-layer) design. Two multilayer configurations, PLLA/PAN-ML and PAN/PLLA-ML, were compared with single-polymer controls to assess how the deposition sequence affects structure, transport, and mechanical performance. Nitrogen adsorption confirmed mesoporosity in the 9.3–13.7 nm range, and multilayers exhibited higher specific surface areas (15.9–16.9 m2/g) than neat PLLA (4.6 m2/g), indicating an improved fluid–matrix interaction. Water absorption values for PLLA/PAN-ML (500%) and PAN/PLLA-ML (430%) were intermediate between PLLA (60%) and PAN (1130%), revealing sequence-dependent hydrophilicity. Water vapor permeability measurements further showed that mass transport is governed by the outermost layer, with PAN/PLLA-ML displaying higher WVP than PLLA/PAN-ML. Tensile tests demonstrated that the multilayer design enhanced stiffness while preserving ductility, yielding Young’s moduli of 18.74 ± 0.98 and 28.08 ± 2.19 MPa for PLLA/PAN-ML and PAN/PLLA-ML, respectively, and the stress–strain response was accurately described by the Yeoh hyperelastic model (R2 > 0.99). After PBS immersion, multilayer scaffolds retained mechanical integrity and exhibited sequence-dependent degradation. In vitro assays with human cells showed higher viability for multilayers than for neat PLLA, supporting their use in tissue-engineering and wound-healing applications. Overall, multilayer electrospinning provides a simple and versatile strategy to simultaneously optimize porosity, wettability/permeability, and mechanical balance in biomedical fibrous scaffolds. © 2025 American Chemical Society